STUDENTS’ ABILITY IN MASTERING READING COMPREHENSION - Rahmatun Nisa; Siti Safura; Deni Fajar Wicoksono (English Education Department, 2018)
Narrative text is one of reading texts should be mastered by the students in learning English. Reading skill is considered as a skill that needs a strong comprehension. Thus, this paper aimed to find out to what extend students understand reading of narrative text; to identify the items of reading skill mastered well by the students in comprehending narrative text; and to examine the method used by the teacher in teaching reading narrative text. The worksheet and interview were applied to analyze the data. The result showed that students’ ability in understanding reading of narrative text is very good. The first aspect of reading which mastered by the students is main idea with 84,44%, the second is reference with 83,89%, the third is detail with 81,11%, the fourth is inference with 80,33% and the last aspect is vocabulary with 66,67%. It concludes that the aspect that mastered well by the students is main idea and the most difficult aspects for the students in reading is vocabulary. Pertaining to interview, teacher taught the students by using many methods in order to avoid the students’ boredom in learning.